On the Possibility of Scientific Socialism. S. N. Bulgakov vs K. Marx - V. B. Aleksandrov (Управленческое консультирование, 2023)
The article deals with criticism by the great Russian philosopher S. N. Bulgakov’s ideas of scientific socialism in his major work “Philosophy of Economics”. Attention is drawn to the fact that Bulgakov’s philosophical basis for this criticism is an indication of the primacy of the theme of justice in a socialist society, which is rationalized in the theory of scientific socialism. Bulgakov shows that in the very history of Marxism, the focus on justice predetermines the desire to build a theory of scientific socialism. Another topic discussed by the philosopher in the framework of his criticism of the idea of scientific socialism is the illegitimacy of Marxism’s assertion about the existence of laws of a natural historical type, in accordance with which the development of society as a whole takes place and which are considered in Marxism as the basis for the possibility of scientific substantiation of the inevitable onset of a future just society. . According to Bulgakov, the scientific nature of social policy is determined by relying not on such laws, but on statistical generalizations, a kind of empirical patterns that express the development trends of certain aspects of social life in specific conditions and in a specific historical period. Another subject of Bulgakov’s criticism is the desire to talk about the development of society as a whole. Scientific research, in his opinion, should be specific and deal with specific aspects of public life. The whole cannot be the subject of scientific research. The article draws attention to the similarity of Bulgakov’s views to the views of K. Popper, set forth by him a quarter of a century after the Russian philosopher in his work “The Poverty of Historicism”. Popper criticizes historicism, by which he understands the concept of the natural development of society as a whole, which inevitably turns into utopianism. Attempts to talk about society as a whole and try to transform it as a whole, he defines as holism, which he contrasts with “partial engineering”. The author of the article notes that the views of these two thinkers, which reveal an undoubted similarity, deserve to be presented in modern discussions about the possibility of social prediction.